Analisis Rasa Nasionalisme Masyarakat Aceh Pasca Konflik Gerakan Aceh Merdeka - Rahma Syakira Ayu; Rizka Luluatul Hasanah; Ronaldo Febryan; Shalwa Azahra; Ardli Johan Kusuma (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This research aims to analyze the sense of nationalism of the Acehnese people after the conflict with the Free Aceh Movement (GAM), as well as finding out how the feeling of "belonging" towards Indonesia was re-formed after the 2005 Helsinki MoU. This research uses a qualitative descriptive approach with literature studies from journals, books, and websites on this topic. The data in this research were analyzed using Realistic Conflict Theory introduced by Sherif, and Belongingness Theory by Beumeister and Leary. The results of this research are that this research shows that the GAM conflict occurred as a result of social, political and economic injustice felt by the people of Aceh. The Helsinki MoU was a turning point, allowing special autonomy and socio-political reintegration of Aceh. After the conflict, the Acehnese people's sense of nationalism and "belonging" began to recover through reconciliation, restoration of basic rights, and participation in local politics. However, challenges in strengthening the "belonging" principle remain, especially regarding economic disparities and trust in the central government. This research concludes that the diplomatic approach, international support, and autonomy policies contributed significantly to re-weaving the ties of Acehnese nationalism within the framework of the Indonesian state.